Impact in Clinical Practice of the European Medicines Agency Health Alert About the Restriction of the Use of JAK Inhibitors - Elisabet Castañeda-Estévez; Cristina Vergara-Dangond; Martina Steiner; Maria Beatriz Paredes-Romero; Ana Esteban-Vázquez; Tatiana Cobo-Ibañez; Laura Trives-Folguera; Maria Liz Romero-Bogado; Isabel De La Cámara-Fernández; Patricia Richi-Alberti; Ana Acosta-Alfaro; Iría De la Osa-Subtil; et al. (Pharmaceuticals)
Background/Objectives: Janus kinase inhibitors (JAKi) have revolutionized the treatment of various inflammatory and immune disorders. Concerns about the potential increased risk of major adverse cardiovascular events (MACEs) associated with JAKi use led to a European Medicines Agency (EMA) health alert recommending restricting the use of JAKi in high-risk populations. Methods: This study aims to determine the proportion of patients who developed any cardiovascular, ischemic, neoplastic, or thrombotic adverse event in a cohort of patients receiving, or who have received, JAKi treatment between January 2017 and September 2023. In addition, we studied the impact of the alert in the clinical practice of our Rheumatology department. Results: In this retrospective, observational study, 101 patients were analysed, predominantly women (72.3%), with a mean age of 57.6 years. The most common diagnoses were rheumatoid arthritis (60.4%) and psoriatic arthritis (18.8%). The most frequent adverse events were infections (5.9%) and neoplasms (2.9%). Deep vein thrombosis and haemorrhagic stroke each occurred in 1% of patients, with no cases of ischemic stroke or ischemic heart disease. When the health alert was published, 75 patients were on treatment with JAKi, and 33 met the alert criteria. Of these, 12.1% changed treatment due to the alert, 9% had no other therapeutic options, 57.5% were in clinical remission or had low disease activity, and 9% maintained treatment at their own request. Conclusions: These findings suggest that, in this patient cohort, JAKi use did not result in new MACE cases. The alert concerning the use of JAKi has had a limited impact in our clinical practice.